Special Aspects in Designing High - Frequency Betatron; Journal of Physics: Conference Series; Vol. 671 : Innovations in Non-Destructive Testing (SibTest 2015) - Filimonov A. A. Anatoly Alekseevich (2016, 2016)
Title screen